World-Building and the Early Modern Imagination - Kavey, A.; Kavey, A. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
The early modern period was rife with attempts to re-imagine the world and the human place within it. This volume looks at natural philosophers, playwrights, historians, and other figures in the period 1500-1700 as a means of accessing the plethora of world models that circulated in Europe during this era.